ATTITUDES OF EFL STUDENTS REGARDING LEARNER AUTONOMY IN ENGLISH VOCABULARY ACQUISITION - I Putu Andre Suhardiana (Yavana Bhasha : Journal of English Language Education, 2021)
Practical English communication for EFL students is wholly based on their vocabulary.However, learner autonomy (LA) is critical for EFL students’ vocabulary acquisition. The purpose ofthis research is to find out the viewpoints of students regarding LA when it comes to acquiringEnglish vocabulary. There were 100 students from the college majoring in English LanguageEducation Department completed the closed questionnaire, and 7 students participated in semistructuredinterviews. The research established that while participants intellectually recognized therelevance of LA in learning English vocabulary, they demonstrated a lack of interest in LA in learningEnglish vocabulary on an emotional and behavioral level. These findings may help explain how toimprove English teaching and learning, particularly English vocabulary teaching, in the context ofother comparable EFL and research.